2021
DOI: 10.3390/ijerph18147294
|View full text |Cite
|
Sign up to set email alerts
|

Living with Long Term Conditions from the Perspective of Family Caregivers. A Scoping Review and Narrative Synthesis

Abstract: (1) Background: When living with one or more long term conditions (LTCs), both the patient and the family experience the impact of the condition at different levels. The family’s needs and perceptions should be considered in the process of caring for people with LTCs. The aim of this review is to understand “the process of living with LTCs” from a family perspective. (2) Methods: A scoping review and narrative synthesis were conducted using a systematic methodology in MEDLINE, CINAHL, Web of Science and PsycIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…Our findings support other studies that identified that the caregivers' emotional trajectories were not static and did not follow a linear pattern (Marín-Maicas et al, 2021;Shiraishi & Reilly, 2019). A previous conceptual model on living with long-term conditions from the patient's (Ambrosio et al, 2015) and the family caregiver's perspective (Ambrosio et al, 2021;Marín-Maicas et al, 2021) described the experience of longterm conditions as a complex, cyclical and dynamic process that includes five attributes: acceptance; coping; self-management; integration and adjustment. In addition, several mechanisms such as changes in the patients' situation or personal circumstances, the existing social network and the perceived support or information could modify the process.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our findings support other studies that identified that the caregivers' emotional trajectories were not static and did not follow a linear pattern (Marín-Maicas et al, 2021;Shiraishi & Reilly, 2019). A previous conceptual model on living with long-term conditions from the patient's (Ambrosio et al, 2015) and the family caregiver's perspective (Ambrosio et al, 2021;Marín-Maicas et al, 2021) described the experience of longterm conditions as a complex, cyclical and dynamic process that includes five attributes: acceptance; coping; self-management; integration and adjustment. In addition, several mechanisms such as changes in the patients' situation or personal circumstances, the existing social network and the perceived support or information could modify the process.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, several mechanisms such as changes in the patients' situation or personal circumstances, the existing social network and the perceived support or information could modify the process. The present study found that this emotional trajectory could change with the course of the illness, and the specific situation of the person with the mental illness may have a clear impact on it (Ambrosio et al, 2015;Marín-Maicas et al, 2021). Moreover, as in previous studies of caregivers of advanced cancer patients (Leow & Chan, 2017), the support received from other family members and friends and health professionals are critical for caregivers.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Furthermore, activating existing resources and creating new resources [16], [34] make the family grow and actively use the resources they have to care for sick family members. This is supported by research [35], [36] that there is a relationship between primary health services and the family role in chronic diseases that require long-term care.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, living with LTCs is not only important for the person affected, but the family caregiver as well. The meaning of living with an LTC, and the dimensions that compose it, are mostly similar between the people with LTC and the family caregivers [ 7 ]. However, two of its dimensions, self-management and integration, have different meanings and applications [ 7 ].…”
Section: Introductionmentioning
confidence: 99%